The 3D Potential Flow Simulation of an Electric Commuter Train's Velocity and Pressure with LISA FEA V.8 - Aco Wahyudi Efendi (Indonesian Journal Of Civil Engineering Education, 2024)
The current research examines the aerodynamic behaviour of an electric commuter rail vehicle moving at 100 km/h by comparing the findings of 3D simulation with manual estimations of dynamic pressure and velocity. Compared to manual approaches, the simulation yielded more accurate insights using the potential flow theory-based LISA FEA V.8 program. There was a 5% discrepancy between the simulation's range of 0.546 kN/m² to 4.865 kN/m² and the manually determined dynamic pressure of 4.633.3 kN/m². The simulation demonstrated the impact of intricate aerodynamic interactions, which produced a velocity of 31.66 m/s, 14% greater than the manual calculation at the train's front of 27.78 m/s.Furthermore, the simulation revealed an uneven velocity distribution contributing to drag, with the highest speeds along the sides and a low-pressure wake at the back. These findings highlight the need for sophisticated simulations to improve train design, lower drag, increase energy efficiency, and improve passenger comfort. They also show the limitations of simplified computations